Factoring Ethics in Technology, Policy Making, Regulation and AI - Hessami, Ali G.; Shaw, Patricia (IntechOpen, 2021)
This book explores the ethical implications of the burgeoning adoption and deployment of Autonomous Decision Making and Algorithmic Learning Systems (ADM/ALS) on human rights and societal values as well as these systems' potential social harms and benefits. After two millennia of recorded civilization, consideration of ethics and social values in all that we strive for is a long-overdue phenomenon. Therefore this is a journey that we've just embarked on thanks to the emergence of ADM/ALS and should not be treated as a destination in line with many other facets and emergent properties of products, services, and systems. This book informs policymakers and practitioners about best practices in technology ethics pertinent to many disciplines and sectors.